EVALUATING THE EFFECTIVENESS OF THE PROBLEM-BASED LEARNING MODEL FOR STUDENTS IN THE ECONOMICS EDUCATION STUDY PROGRAM - Astuti, Vera; Purnamasari, Niken (Universitas Negeri Yogyakarta, 2025)
This study investigates the impact of Problem-Based Learning (PBL) on student learning outcomes in an introductory accounting course within the Education Economics program. Utilizing a One-Group Pre-test Post-test Design, the research measures students' performance before and after implementing the PBL model. The results indicate a significant improvement in mean scores, rising from 83.1509 to 91.7547, with a p-value of 0.000, suggesting that PBL effectively enhances students' academic achievement. The study also explores the reasons behind PBL's effectiveness, highlighting its promotion of active engagement, critical thinking, collaboration, and the application of knowledge to real-world situations. These findings underscore the value of incorporating PBL into educational practices to improve both cognitive and non-cognitive learning outcomes.